Pratylenchus brachyurus (Godh) Filipjev. & Stekhoven is one of the importantplantparasitic nematodes that attacked root of patchouli and the causal of mot necrosis, growth retardation, reddish or yellowish leaf: A greenhouse study was conducted to evaluate the level of resistant of six patchouli cultivars, those were wide planted in Sumatera against P. brachyurus, and to determine the effect of population level of the nematodes on three dzrerent resistance patchouli. Six patchouli cultivars were - Rina Sriwati; Meity S. Sinaga; Abdul Muin Adnan' Ika Mustika (Buletin Hama dan Penyakit Tumbuhan, 1999)
Pratylenchus brachyurus (Godh) Filipjev. & Stekhoven is one of the importantplantparasitic nematodes that attacked root of patchouli and the causal of mot necrosis, growth retardation, reddish or yellowish leaf: A greenhouse study was conducted to evaluate the level of resistant of six patchouli cultivars, those were wide planted in Sumatera against P. brachyurus, and to determine the effect of population level of the nematodes on three dzrerent resistance patchouli. Six patchouli cultivars were inoculated with 200 nematodes& soil. Based on reproduction index the cultivar of Seulimum Putih, Pidie and Sidikalang known as susceptible ones Tapaktuan and Seulimum Merah was moderate resistant and Girilaya was resistant. Furthermore, the effect of population levels of P. brachyurus (0, 100, 200 and 800 nematodes& soil) on three patchouli cultivars showed that 200 nematodeskg soil population caused significant effect on reduced shoot and weight root and plant height on susceptible cultivars, howevec on the moderat resistant and resistant cultivar the signifcance effect occurred at 800 nematodeslkg soil. The reproduction factors on three patchouli cultivars were decreased with the increased of population nematodes level. me oil and chlorophyll content have been decreased on the infectedpatchouli cultivars atfive month afCer inoculation.